Rethinking territorial disputes in the South China Sea : transforming problem into opportunity - Dato’ Muthiah Alagappa (2012)
The disputes in the East and South China Seas have not led to war so far, but they can stoke competitive nationalisms and strategic alignments with worrying consequences for regional peace and security. Yet, they present an opportunity to construct a rules-based order grounded in principles and guided by an effective management regime and dispute settlement mechanism.